Application of graphene oxide nanosheets and HPAM aqueous dispersion for improving heavy oil recovery: Effect of localized functionalization. (1st April 2020) - Aliabadian, Ehsan; Sadeghi, Soheil; Rezvani Moghaddam, Amir; Maini, Brij; Chen, Zhangxin; Sundararaj, Uttandaraman
Abstract: Using efficient methods to recover heavy oil is crucial for economic success. Polymer flooding is a very efficient way to sweep oil reservoirs at both macroscopic and microscopic scales by increasing the viscosity of injected water. Recently, it was shown that addition of nanomaterials to polymer solutions may improve the flooding performance and recovery. In this work, two different types of graphene oxide (GO) nanofillers with different different location of OH group functionalization (functionalization mainly on basal plane (S-GO) and functionalization mainly on the edges (E-GO)) were synthesized to improve the rheological behavior and oil recovery efficiency of a partially hydrolyzed polyacrylamide (HPAM) solutions. To characterize the chemical structure of both GOs, thermogravimetric analysis (TGA) and Raman spectroscopy were employed. Frequency sweep, creep, creep recovery, shear start-up, and strain sweep tests were also utilized to evaluate the viscoelastic behavior of HPAM solutions, with or without the nanofillers in both linear and nonlinear viscoelastic regions. Cryo-SEM images of the hybrid dispersion of HPAM/GOs were captured to assess the dispersion state of all systems. A core flooding set up was used to evaluate the effectiveness of all dispersions in improving the viscous oil recovery by polymer injection. Rheological properties showed that addition of 0.2 wt% of both GOs reduced dynamic moduli. However, due to the better dispersion of S-GO in a HPAM solution, incorporation of 0.2 wt% of S-GO to the HPAM solution, improved the oil recovery by 7.8% compared to the HPAM solution.